The orbitofrontal cortex projects to the parvafox nucleus of the ventrolateral hypothalamus and to its targets in the ventromedial periaqueductal grey matter - Babalian, Alexandre; Alvarez-Bolado, Gonzalo (Brain structure & function, 2019)
Although connections between the orbitofrontal cortex (OFC)—the seat of high cognitive functions—the lateral hypothalamus and the periaqueductal grey (PAG) have been recognized in the past, the precise targets of the descending fibres have not been identified. In the present study, viral tracer-transport experiments revealed neurons of the lateral (LO) and the ventrolateral (VLO) OFC (homologous to part of Area 13 in primates) to project to a circumscribed region in the ventrolateral hypothalamus, namely, the horizontally oriented, cylindrical parvalbumin- and Foxb1-expressing (parvafox) nucleus. The fine collaterals stem from coarse axons in the internal capsule and form excitatory synapses specifically with neurons of the parvafox nucleus, avoiding the rest of the hypothalamus. In its further caudal course, this contingent of LO/VLO-axons projects collaterals to the Su3- and the PV2 nuclei, which lie ventral to the aqueduct in the (PAG), where the terminals fields overlap those deriving from the parvafox nucleus itself. The targeting of the parvafox nucleus by the LO/VLO-projections, and the overlapping of their terminal fields within the PAG, suggest that the two cerebral sites interact closely. An involvement of this LO/VLO-driven circuit in the somatic manifestation of behavioural events is conceivable.
Published online: 12 October 2018
Gesehen am 28.10.2019